Media Framing of Women's Football During the COVID-19 Pandemic. (June 2023) - Parry, Keith D.; Clarkson, Beth G.; Bowes, Ali; Grubb, Laura; Rowe, David
This article examines British media coverage of women's association football during the coronavirus (COVID-19) pandemic, to identify how the media framed the women's game and how these frames could shape the public perceptions of it. Through a database search of British-based news coverage of women's football, 100 news articles were identified in the first 6 months after the start of the pandemic. A thematic analysis was conducted, and five dominant frames were detected in the context of COVID-19: 1) financial precariousness of women's football ; 2) the commercial prioritisation of men's football ; 3) practical consideration of the sport (e.g., alterations to national and international competitions); 4) debating the future of women's football and 5) concern for players (e.g., welfare, uncertain working conditions). These frames depart from the past trivialisation and sexualisation of women's sport, demonstrate the increased visibility of women's football, and shift the narrative towards the elite stratum of the game. Most of this reporting was by women journalists, while men were shown to write less than women about women's football. This research advocates continued diversification of the sports journalism workforce to dissolve the hegemonic masculine culture that still largely dominates the industry.